2019
DOI: 10.1016/j.cub.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Behavioral and Physiological Responses to a Social Signal Are Regulated by a Shared Neuronal Circuit

Abstract: Highlights d C. elegans male pheromone promotes hermaphrodite reproductive success d Serotonin is required for hermaphrodites to respond to male pheromone d The same neuronal circuit mediates behavioral and physiological responses d Circuit sharing coordinates distinct phenomena occurring on different timescales

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(75 citation statements)
references
References 52 publications
4
71
0
Order By: Relevance
“…The results showed that hermaphrodites from TR389 male-conditioned medium had higher mating efficiency compared to those from hermaphrodite-conditioned medium (Fig. 2I), which is consistent with previous research that the male environment reduces hermaphrodites exploration and increases mating behaviors (Aprison and Ruvinsky, 2019a, b). Interestingly, we found that N2 male-conditioned medium showed a significant further increase of hermaphrodite mating efficiency than the TR389 male-conditioned medium (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The results showed that hermaphrodites from TR389 male-conditioned medium had higher mating efficiency compared to those from hermaphrodite-conditioned medium (Fig. 2I), which is consistent with previous research that the male environment reduces hermaphrodites exploration and increases mating behaviors (Aprison and Ruvinsky, 2019a, b). Interestingly, we found that N2 male-conditioned medium showed a significant further increase of hermaphrodite mating efficiency than the TR389 male-conditioned medium (Fig.…”
Section: Resultssupporting
confidence: 91%
“…An interesting possibility has recently been proposed in the context of ascr#10-mediated suppression of exploration. The male-specific ascr#10 reduces exploratory behavior in hermaphrodites in part via increased serotonergic signaling ( Aprison and Ruvinsky 2019a ). Reduced roaming enhances mating success ( Aprison and Ruvinsky 2019a ), suggesting a plausible physiological relevance for the ascaroside-mediated suppression of foraging.…”
Section: Pheromone Signal Transduction In the Regulation Of Behaviormentioning
confidence: 99%
“…The apparent coalescence of these two sets of environmental cues on ASI/DAF-7 raises the question of whether that neuron is unique in communication with the germ line or its niche. However, the effect of ascr#10 has also been shown to require serotonin, specifically serotonin produced in response to the pheromone by HSN and NSM neurons via the expression of tph-1 [ 75 ]. This signal requires the serotonin receptor gene mod-1 , and mod-1 mutants can be rescued for their ability to respond to ascr#10 by restoring mod-1 function to neurons AIY or RIF, but not to ASI [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the effect of ascr#10 has also been shown to require serotonin, specifically serotonin produced in response to the pheromone by HSN and NSM neurons via the expression of tph-1 [ 75 ]. This signal requires the serotonin receptor gene mod-1 , and mod-1 mutants can be rescued for their ability to respond to ascr#10 by restoring mod-1 function to neurons AIY or RIF, but not to ASI [ 75 ]. Remarkably, the potentiation of adult hermaphrodites to respond to ascr#10 requires egg laying activity via a mechanism that reports reproductive status through the vm2 muscles to the nervous system [ 112 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation